Exploration of Ethnobiotechnology in East Java Indonesia for Learning Scientific Writing : Originality and Implications - Subekti, Hasan; Purnomo, Aris Rudi; Suwandi, Edi (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to represent the preferences of similarity index in student work on Ethnobiotechnology exploration practices in East Java and its implications in the learning context. A quasi-quantitative approach is applied, presenting the results in a descriptive-interpretive manner. Documentary techniques are used as instruments for data collection from 21 scientific papers produced by prospective science teachers in East Java that discussed Ethnobiotechnology practices. The Turnitin application is used to validate manuscript similarities and maintain academic integrity. Furthermore, Scopus AI is used to analyze research implications, which are then rearticulated using keywords and schematized as a concept map. The findings show that nine articles (42.9%) are categorized as Orange, indicating a high level of similarity, nine articles (42.9%) are categorized as Yellow, indicating a moderate level of similarity, and only three articles (14.2%) are categorized as Green, indicating low similarity and considered more original. This study concludes that students' work preferences in exploring Ethnobiotechnology in East Java tend to have a high to moderate level of similarity. Despite this, the study offers valuable insights into integrating cultural practices with scientific research and lessons, academic ethics, and plagiarism detection. The research has implications for science dissemination in the context of scientific writing ethics and the use of plagiarism detection applications for future science learning development.